The Relationship Between Self Control and Nomophobia in Nursing Students - Juliana Hidayati; Efri Widianti; Lia Nurlianawati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
The sophistication of smartphone technology is growing rapidly and provides convenience in all aspects as well as an important need which is also popular among all circles including students, which unconsciously makes them feel anxious if they are far from their smartphone or what is called nomophobia, but there are factors that affect nomophobia, one of them self control. Self-control is very important in one's life, it functions as self-control over behavior in everyday life. The purpose of this study is to analyze the relationship between self-control and nomophobia in undergraduate nursing students. This research method is correlational. The population amounted to 614 people with a proportional stratified random sampling technique and the number of samples that had to be taken was 86 people. Data collection uses a self-control scale adapted from vindabayu(2016) validity coefficient between 0.383-0.718 and reliability 0.928 and the nomophobia questionnaire adapted from (Putri, 2019) validity coefficient between 0.332-0.805 and reliability 0.924. The data analysis of this research is univariate analysis using frequency distribution and bivariate using spearman rank. The results showed that the level of self-control in undergraduate nursing students was classified as moderate as many as 62 students. with a p-value of 0.048, it can be concluded that there is a significant negative relationship between self-control and nomophobia in undergraduate nursing students.